The relation of mathematics attitudes, locus of control, and gender with the mathematics achievement of Catholic high school seniors in Metro Manila - Adefuin, John Jaworski N. (Animo Repository, 1992)
This study investigates the relationship of mathematics attitudes, locus of control and gender with mathematics achievement of Catholic high school seniors in Metro Manila. The study employs the descriptive-correlational and comparative methods as its research design. The study involved 260 male and female high school seniors from three Catholic schools in Metro Manila, namely: Colegio de San Agustin, Saint Scholastica's College and San Beda College as its respondents. The instruments used for data gathering were a) Mathematics Achievement Test, b) Mathematics Attitude Inventory, and c) Locus of Control Scale. The results showed that males (M = 42.00) and females (M = 41.83) students fell within the average category of the mathematics achievement. The mathematics attitudes of males (M = 110.46) and females (M = 105.69) students fell within the positive category. The males (M = 11.78) and females (M = 11.68) students' locus of control was average. Meanwhile, there was no significant differences in males' and females' mathematics achievement (t(258) = 0.19, p .05), mathematics attitudes (t(258) = 1.81, p .05) and locus of control (t(258) = .171, p .05). On the other hand, there was a low but significant positive relationship between mathematics attitudes and mathematics achievement (r = .315, p .01) a significant but low negative correlation between locus of control and mathematics attitude (r .05). Eventually, the best predictor of mathematics achievement is mathematics attitudes (R2 = .099), although it has a minimal contribution. At the same time, it was found that gender is not a moderator variable in the relationship between mathematics attitude and mathematics achievement, locus of control and mathematics achievement, mathematics attitudes and locus of control. In conclusion, gender does not play a role in the mathematics achievement and mathematics attitudes of males and females. That mathematics attitudes predicts mathematics achievement to some extent but locus of control and gender do not. Finally, other variables may be more predictive of mathematics achievement than mathematics attitudes, locus of control and gender.